Advanced subclinical atherosclerosis: A novel category within the cardiovascular risk continuum with distinct treatment implications - Michael J. Blaha; Magdy Abdelhamid; Francesca Santilli; Zhongwei Shi; Dirk Sibbing (Elsevier, 2023)
Traditionally, guidelines divide patients into primary and secondary prevention for atherosclerotic cardiovascular disease (ASCVD) risk management. However, the modern understanding of the biological progression of atherosclerosis is inconsistent with this binary approach. Therefore, a new approach demonstrating both atherosclerosis and ASCVD risk as a continuum is needed to give clinicians a framework for better matching risk and intensity of therapy. Advances in coronary imaging have most clearly brought this problem into view, as for example coronary artery calcium (CAC) scoring has shown that some individuals in the primary prevention have equal or higher ASCVD risk as certain subgroups in secondary prevention. This article introduces "advanced subclinical atherosclerosis" as a new and distinct clinical group that sits between the traditional groups of primary and secondary prevention. Importantly, this article also introduces a new graphic to visualize this intermediate population that is explicitly based on plaque burden. The aim of the graphic is both to educate and to allow for better identification of a patient's cardiovascular risk and guide more effective risk-based management.